Gas mixing caused by interacting heat sources PART I: Experiments - Paranjape, Sidharth; Kapulla, Ralf; Mignot, Guillaume; Paladino, Domenico (Nuclear engineering and design, 2020)
•Experimental data on the combined effect of containment wall condensation and PAR thermal effect.•Wall condensation enhances gas mixing, transporting hydrogen to PAR inlets at lower levels.•PAR located at lower elevation dominates the gas mixing driving force.•Plume generated by PAR significantly enhance the momentum of a steam jet leading to gas mixing. The four experiments presented in this paper investigate the influence of the plumes released by the operation of one or two heat sources located at different elevations, on the erosion of a stratified gas atmosphere in the presence of steam condensation on vertically oriented cooled pipes. The heat sources are located at two different elevations in a vessel with 4 m diameter and 8 m height, and they represent Passive Autocatalytic Recombiners (PARs) in a Light Water Reactor (LWR) containment and the heat PARs would release. The condensation on the cooled tubes represents the condensation which would take place during postulated accident scenarios at the concrete wall of a real containment. The condensation on the tubes contributes to the large-scale convection loops and enhances the gas mixing caused by the rising plumes from the heat sources. The stratification with a helium-rich layer – the helium represents hydrogen in a real containment – was created by a vertical steam and steam-plus-helium jet interacting with a circular disk located 1 m above the jet exit. Temperature, gas concentration and velocity field measured during the experiments showed that the activation of only the upper heater created a homogeneous gas mixture above the level of the heater, while forming a sharp concentration gradient below it. By operating only the lower heater, the emerging plume homogenized the entire vessel at the end of the test, showing that it was more effective in gas mixing. The simultaneous activation of the upper and the lower heaters accelerated the breakup of the helium stratification. The experiments were performed in the PANDA facility in Switzerland in the frame of the OECD/NEA HYMERES project which is focused on the hydrogen safety issues related to Light Water Reactors, specifically to hydrogen distribution in the containment. The experiments presented in the present paper were analyzed with the GOTHIC code which is the subject of Part II of this article.